The Usefulness of Genotyping of Celiac Disease-Specific HLA among Children with Type 1 Diabetes in Various Clinical Situations. (22nd February 2020) - Deja, Grazyna; Sikora, Dominika; Pyziak-Skupien, Aleksandra; Klenczar, Karolina; Deja, Rafał; Jarosz-Chobot, Przemysława
Abstract : Aim . The aim of the study was to determine the usefulness of HLA DQ2/DQ8 genotyping in children with T1D in various clinical situations: as a screening test at the diabetes onset, as a verification of the diagnosis in doubtful situations, and as a test estimating the risk of CD in the future. Materials and methods . Three groups of patients with T1D were included: newly diagnosed (n = 92 ), with CD and villous atrophy (n = 30 ), and with potential CD (n = 23 ). Genetic tests were performed (commercial test, PCR, and REX), and clinical data were collected. Results . The results of genetic tests confirmed the presence of DQ2/DQ8 in 94% of children with diabetes (group I) and in 100% of children with diabetes and CD (groups II and III, respectively). Comparative analysis of the HLA DQ2/DQ8 distribution did not show any differences. Allele DRB 1 ∗ 04 (linked with HLA DQ8) was significantly less common in children with diabetes and CD (group I versus groups II and III, 56.5% vs. 24.5%; p = 0.001 ). The probability of developing CD in DRB 1 ∗ 04 -positive patients was 4 times lower (OR 0.25; 95% CI 0.118-0.529; p = 0.001 ). DRB 1 ∗ 04 was significantly less frequent in children with villous atrophy compared to potential CD (13% vs. 39%; p = 0.03 ). Conclusions . Genotyping HLA DQ2/DQ8 as a negative screening has limited use in assessing the risk of CD at the diabetes onset and does not allow to verify the diagnosis of CD in doubtful situations. The presence of the DRB 1 ∗ 04 allele modulates the risk of CD and significantly reduces it and can predict a potential form.